The effectiveness of promotional activities towards creating customer awareness at Melaka International Trade Centre (MITC) / Suhailey Hussin - Hussin, Suhailey (Faculty of Business and Management, 2007)
This research is about a study on effectiveness of promotional activities towards creating customer awareness at Melaka International Trade Centre (MITC). Factors such as advertising, sales promotion, personal selling, publicity and direct marketing have been identified in order to investigate whether or not these factors have a relationship with customer awareness. The survey is conducted at Melaka area. The sample size for this study is 50 customers from Melaka International Trade Centre (MITC). There were 50 questionnaires were distributed and all 50 questionnaires were returned. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that contain element that potentially have relationship with customer awareness. Data are analyzed using Reliability Test, Pearson Correlation Analysis, Frequency Analysis and Descriptive statistics through SPSS Program. The result shows that all five promotional activities which advertising, sales promotion, personal selling , publicity and direct marketing have significant relationship on customer awareness.